Dialektika Hukum dan Identitas dalam Perubahan Nama di Pengadilan Negeri Gorontalo - Nijam Hiliwilo; Fence M. Wantu; Mohamad Hidayat Muhtar (Perkumpulan Maju Karya Yogyakarta, 2025)
This research discusses Decision Number 67/Pdt.P/2024/PN Gto at the Gorontalo District Court regarding a request to change a child's name from